2011
DOI: 10.1186/1477-7819-9-13
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumors: correlation between symptoms at presentation, tumor location and prognostic factors in 47 consecutive patients

Abstract: BackgroundGastrointestinal stromal tumors (GIST) are mesenchymal tumors of the gastrointestinal tract, usually kit-positive, that are believed to originate from interstitial cell of Cajal, or their related stem cells. The most common clinical presentation of these tumors is gastrointestinal bleeding, otherwise they may cause intestinal obstruction, abdominal pain, a palpable mass, or can be incidentally detected during surgery or endoscopic/radiological procedures. Prognosis is related to the size of the tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 40 publications
6
87
3
3
Order By: Relevance
“…Stomach is the most common site with 60%, while small bowel constitutes 20-30% in western countries (20,21). Studies from Japan also supports stomach as the most common site (up to 70%) (22).…”
Section: Discussionmentioning
confidence: 99%
“…Stomach is the most common site with 60%, while small bowel constitutes 20-30% in western countries (20,21). Studies from Japan also supports stomach as the most common site (up to 70%) (22).…”
Section: Discussionmentioning
confidence: 99%
“…Although 60% of GISTs occur in the stomach whilst only 20-30% occur in the small intestine (28), NF1-related GISTs (NF1-GIST) tend to be located in the small intestine (28). The pathogenesis of NF1-GIST is different to that of sporadic GIST.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Caterino and his co-workers who demonstrated an association between diminished survival and emergency presentation of GISTs, both patients who received emergency resection survived during entire follow up period. 15 An analysis of data from ten population-based studies revealed that the 5-year recurrence-free survival rates for GISTs treated with surgery alone was approximately 70%. 15 The median postoperative follow up period was 21 (range: 8-48) months.…”
Section: Discussionmentioning
confidence: 99%
“…15 An analysis of data from ten population-based studies revealed that the 5-year recurrence-free survival rates for GISTs treated with surgery alone was approximately 70%. 15 The median postoperative follow up period was 21 (range: 8-48) months. Overall, 13 patients (87%) among the study cohort while 10 patients (67%) had recurrence-free survival.…”
Section: Discussionmentioning
confidence: 99%